Cavernous lymphangioma of eyelid - a rare case report - Kumar, Sanjiv; Kumar, Sandeep; Malik, VK; Jain, K; Jain, C; Kamboj, R; Bansal, R (Nepalese Journal of Ophthalmology, 2011)
Background: Lymphangioma is a lymphatic malformation, a benign proliferation of lymph vessels. Case: We hereby present a case of eyelid lymphangioma of cavernous type in a twelve year old male patient. This is a very uncommon site for this type of lymphangioma. Key words: lymphangioma, eyelid, cavernous type DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5278 Nepal J Ophthalmol 2011; 3(2): 196-198